Assessment of the degree of conjugacy of voluntary EMG activity of muscles and thresholds of heat perception in patients with spinal deformity - M. A. Bogatyrev; M. S. Saifutdinov; E. N. Shchurova (Acta Biomedica Scientifica)
The occurrence of combined sensorimotor disorders of spinal cord function in combination with disorders of the autonomic nervous system after surgical correction of spinal deformity requires studying the mechanisms of the relationship between the sensorimotor and autonomic nervous systems in conditions of iatrogenic disorders.The aim. To identify possible connections and their nature between the thresholds of heat perception and the amplitude of electrical activity of muscles at their maximal voluntary tension in patients with scoliosis for further use as a clinical model for studying the relationship between sensorimotor and autonomic nervous systems.Materials and methods. Eighty-seven patients aged 6–43 years with spinal deformities of various etiologies were examined by electromyography and esthesiometry before and after its surgical correction.Results. Based on the comparison of the electromyogram amplitude at the maximal voluntary tension of the anterior tibial muscle and the thresholds of heat perception, the presence of a reflex apparatus of conjugating the sensitivity to heat of the skin receptive field and voluntary activation of the muscle during localization of its motor neuron pool in the same segment of the spinal cord was established. This reflex mechanism can be used as a basic physiological model to study the nature of the interaction of spinal motor and autonomic centers in conditions of ischemic spinal cord injury during surgical correction of spinal deformity. It is possible to create diagnostic tests on its basis to assess the degree of violations of the interaction of the sensorimotor and autonomic systems in conditions of iatrogenic spinal cord injuries.